The Emergence of Muge Mesolithic Shell Middens in Central Portugal and the 8200 cal yr BP Cold Event - Bicho, Nuno (2017)
The emergence of Portugal’s Muge Mesolithic, with its characteristic shell middens and human burials, is widely seen as a response to the formationofahighly diverse terrestrialandaquatic ecotone inthe Tagus basin by the Flandrian transgression. Recently, some have suggested that this was an adaptive response to the 8200 cal yr BP event. Using the available radiocarbon data for the shell middens, paleoclimatic data, and paleoceanographic datawe present anewmodel for the appearance of the Muge Mesolithic shell middens and changes in settlement between the Boreal and Atlantic phases for central Portugal. Coastal ecosystems were altered due to diminution in upwelling and the occurrence of the 8.2 kyr cold event, with declining availability of marine resources, rapid sea level rise, and changes in coastal morphology. The result was that the previous coastal setting was no longer suitable for the hunter-gatherer-fishers causing a settlement shift to the new, large and stable estuary of the Tagus Valley.